Tonal Neutralization of Taiwanese Checked and Smooth Syllables: An Acoustic Study. (September 2019) - Chien, Yu-Fu; Jongman, Allard
Taiwanese tonal alternation is realized in a circular chain shift fashion for both smooth and checked syllables. Debate regarding the processes of less productive Taiwanese tonal alternation has centered on whether a surface tone is derived from an underlying tone, or whether a surface tone is selected without undergoing any derivation. The current study investigates this controversial issue by examining Taiwanese checked tone and smooth tone sandhi neutralization in production. In particular, we analyzed whether checked citation and sandhi tone 53 (C21→C53), checked citation and sandhi tone 21 (C53→C21), smooth citation and sandhi tone 55 (S51→S55), and smooth citation and sandhi tone 21 (S33→S21) are acoustically completely neutralized in fundamental frequency (F0) height, contour, and duration. A non-sandhi exception was also included to evaluate the effect of position-in-word on F0 height and duration given that citation tones always appear in phrase-final position. Any trace of influence from the underlying representation would indicate a computational mechanism, whereas the absence of any trace would suggest a lexical mechanism for the production of Taiwanese tonal alternation. Results did not show any influence of F0 height, F0 contour, or tone duration from the underlying representation for both checked and smooth tones, supporting a lexical mechanism in speech production for less productive tonal alternations.